Method of local interchange for the investigation of gossip problems: part 2 - Volyam H. Hovnanyan; Suren S. Poghosyan; Vahagn S. Poghosyan (АН Арм. ССР)
The method of construction of Gossip graphs providing a full information exchange with minimal number of calls in minimum time is described. The basis for the graphs of the presented class is the subgraph of canonical form obtained from NOHO graphs by applying the operation of local interchange on them developed by us in [19]. Keywords: Graphs, Networks, Telephone problem, Gossip problem.
Keywords: Mathematics; Computer software